Analysis of Hepatic Lentiviral Vector Transduction: Implications for Preclinical Studies and Clinical Gene Therapy Protocols - Peirong Hu; Yajing Hao; Wei Tang; Graham H. Diering; Fei Zou; Tal Kafri (Viruses)
Lentiviral vector-transduced T cells were approved by the FDA as gene therapy anti-cancer medications. Little is known about the effects of host genetic variation on the safety and efficacy of the lentiviral vector gene delivery system. To narrow this knowledge gap, we characterized hepatic gene delivery by lentiviral vectors across the Collaborative Cross (CC) mouse genetic reference population. For 24 weeks, we periodically measured hepatic luciferase expression from lentiviral vectors in 41 CC mouse strains. Hepatic and splenic vector copy numbers were determined. We report that the CC mouse strains showed highly diverse outcomes following lentiviral gene delivery. For the first time, a moderate correlation between mouse-strain-specific sleeping patterns and transduction efficiency was observed. We associated two quantitative trait loci (QTLs) with intrastrain variations in transduction phenotypes, which mechanistically relates to the phenomenon of metastable epialleles. An additional QTL was associated with the kinetics of hepatic transgene expression. Genes found in the above QTLs are potential targets for personalized gene therapy protocols. Importantly, we identified two mouse strains that open new directions for characterizing continuous viral vector silencing and HIV latency. Our findings suggest that wide-range patient-specific outcomes of viral vector-based gene therapy should be expected. Thus, novel clinical protocols should be considered for non-fatal diseases.